How Christianity came to China : a brief history - Lodwick, Kathleen L. (Minneapolis, Fortress Press, 2016)
Foreign missionaries who served in China ran the gamut of Christians, with differing views of their religion and differing ideas how of to spread it. When all foreign missionaries were forced to leave China in 1949 many thought their effort had been in vain. Yet some scholars predict that soon China will be the country with the largest Christian population in the world. Kathleen L. Lodwick tells the story of Christianity in China. It's essential reading for anyone wanting to understand the contemporary phenomena that is Christianity in China.
Chronology -- Denominationalism -- Sociopolitical -- Geographic -- Missionary and Chinese Christian biographies -- Four theological issues in the China missions.
Includes bibliographical references (pages 233-240) and index.
Keywords: Missions -- China; Christianity -- China; China -- Church history; Church history